Prevalence and determinants of medicinal plants utilization during labour among women of reproductive age in Butiama, Tanzania: A community-based cross-sectional study - Magnus Michael Sichalwe; Nangi William Nangi; Leah Daniel; JohnPaul Otuomasiri Egbobe; Grace Tavengana (PLoS ONE, 2025)
Background The use of certain medicinal plants during childbirth has been linked to negative outcomes such as uterine rupture and foetal distress, both globally and in Sub-Saharan Africa including Tanzania. Despite this, little is known about the factors influencing women’s use of medicinal plants during labour or delivery in Tanzania. This study sought to assess the prevalence and determinants of medicinal plants use during labour and/or delivery in the Butiama district. Methodology This community-based quantitative study used a cross-sectional design with 398 participants, selected through multistage sampling. Data were collected via a structured questionnaire in Swahili language using the Kobo Toolbox from June to July 2024. Analysis was performed with SPSS version 27.0, including checks for completeness before data entry. Descriptive statistics were computed for univariate analysis, while bivariate analysis, conducted through cross-tabulation, determined relationships between variables. Multivariate logistic regression identified significant predictors at p < 0.05. Results In a study of 398 participants, 233(58.5%) reported using medicinal plants during labour and/or delivery. Peasants and homemakers had 2.6 times higher odds of using medicinal plants than those in formal employment (AOR = 2.584, 95% CI: 1.249–5.349, p = 0.011). Women with one child were 1.8 times more likely to use medicinal plants than those with two or more children (AOR = 1.823, 95% CI: 1.136–2.926, p = 0.013). Women within five kilometres of a health facility had 47.7% lower odds of using medicinal plants compared to their counterparts (AOR = 0.523, 95% CI: 0.334–0.819, p = 0.005). Married and cohabiting women were 42.1% less likely to use medicinal plants than divorced/separated/widowed women (AOR = 0.579, 95% CI: 0.338–0.990, p = 0.046). Women with fewer than four antenatal visits were 55.6% more likely to use medicinal plants compared to those with four or more visits. (AOR = 0.556, 95% CI: 0.365–0.848, p = 0.006). Conclusion Over fifty percent of participants reported using medicinal plants during childbirth, with socio-economic status and healthcare access factors suggesting that targeted education and interventions around medicinal plant use would be beneficial.